2021
DOI: 10.2147/jpr.s303536
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Temporomandibular Disorder

Abstract: Temporomandibular disorders (TMD) are a group of diseases in the oral and maxillofacial region that can manifest as acute or chronic persistent pain, affecting millions of people worldwide. Although hundreds of studies have explored mechanisms and treatments underlying TMD, multiple pathogenic factors and diverse clinical manifestations make it still poorly managed. Appropriate animal models are helpful to study the pathogenesis of TMD and explore effective treatment measures. At present, due to the high cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 97 publications
0
17
0
2
Order By: Relevance
“…Pain research to investigate its mechanism has shown significant progress with the establishments of preclinical models [ [14] , [15] , [16] , [17] , [96] , [97] , [98] ]. In particular, behavioral alterations of nociception have been key indicators for the investigation of the similarity between animals and human pain.…”
Section: Neural Mechanisms For Pain In the Deep Craniofacial Tissues In Animalsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pain research to investigate its mechanism has shown significant progress with the establishments of preclinical models [ [14] , [15] , [16] , [17] , [96] , [97] , [98] ]. In particular, behavioral alterations of nociception have been key indicators for the investigation of the similarity between animals and human pain.…”
Section: Neural Mechanisms For Pain In the Deep Craniofacial Tissues In Animalsmentioning
confidence: 99%
“…As TMD pain is multidimensional experiences, preclinical models need to possess such characters. It is, however, difficult to incorporate those into a single animal model [ [15] , [16] , [17] ]. Researchers have often picked one or two risk factors like local injury (e.g.…”
Section: Neural Mechanisms For Pain In the Deep Craniofacial Tissues In Animalsmentioning
confidence: 99%
See 3 more Smart Citations